Character Building of Discipline in the Surau of Students at Yayasan Amal Saleh, Padang City - Hendrawati, Sarah; Wardefi, Riza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study is motivated by the importance of character education in developing students’ discipline through religious-based activities. The research aims to describe the forms of disciplinary character development among students at the Surau of Yayasan Amal Saleh Padang City, identify problems related to discipline in the implementation of congregational Subuh prayer, and analyze the efforts made to overcome these problems. This study employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The results show that disciplinary character development is implemented through habituation, role modeling, regulations, and supervision of religious activities, especially congregational Subuh prayer. The main obstacles include students’ lack of self-awareness, fatigue due to academic activities, and inconsistent time management. Efforts to address these challenges involve guidance, motivation, and strengthening supervision. In conclusion, the Surau plays a significant role in fostering students’ disciplinary character through structured and continuous religious guidance.